Channel modeling and simulated for broadband satellite - Nukfron, Ekavit; Sitichepak, Suviporn (My University, 2009)
This paper presented the effects of attenuation from rain rate together with rain drop size distribution analysis on the model of transmitter broadband satellite in Ka-band frequency. We illustrated a new model by simulating transmission broadband signal and studied the rain attenuation which has effects to high frequency. The results of the model were represented by the relation between error probability and S/N. Moreover, the numbers of re-transmission cycles for completing the amount of data were also presented. The attenuation would be illustrated in log normal distribution forms and in PDF terms. The simulation would be run by taking error probability (Pe) of noise at 0.4, 0.04, 0.004 and 0.004. © 2009 IEEE.
Keywords: Broadband satellite; Ka-band